NEC4 : effective preparation and management of the construction programme - Willis, Tim (Emerald Publishing Limited, 2025)
NEC4: Effective Preparation and Management of the Construction Programme explains the critical role of the programme within the NEC4 suite of contracts, providing insight and guidance into NEC4 contract requirements and good practice in the preparation of planning the works and the programme. The book describes the vital role of the Accepted Programme, both as a contract document, and also as a fundamental tool in contractual procedures, such as its use in assessing changes to planned completion in close to real time, and its use in risk allocation. It includes coverage of key roles of the Client, Contractor and Project Manager in preparing, updating and using the Accepted Programme, and together the chapters provide a sound basis for those preparing and administering the programme in the NEC4 Engineering and Construction Contract (ECC). It is also relevant to users of the NEC4 Professional Services Contract (PSC), the NEC4 Term Service Contract (TSC), and the less onerous programming for the ECC short form. NEC4: Effective Preparation and Management of the Construction Programme is an essential guide for anyone involved with NEC projects to help them understand the importance of properly managing the contract programme, including professionals involved in preparing an NEC contract, Project Managers who administer the programme, and contractors who must prepare and update them.
Keywords: NEC4. -- Engineering and construction contract.; Construction industry -- Management.; Project management.; Business & Economics -- Industries -- Construction.; Construction and heavy industry.; elektronické knihy; electronic books